Legal Protection of Intellectual Property Rights in the Field of Trademarks Registered in Indonesia - Mustomi, Otom; Trisista, Ratna Galuh Manika; Haris, Abdul; Solehudin, Rd. Heri (AMCA, 2025)
Legal protection of trademark rights in Indonesia in implementing the TRIPs agreement based on Law No. 20 of 2016 concerning Trademarks and Geographical Indications. The research aims to analyse the forms of legal protection for registered trademarks in Indonesia and how the government attempts to prevent the emergence of trademark counterfeiting. The scope of research concerns the legal protection of trademark rights in Indonesia. The research method uses normative qualitative research methods. Research results show that the significance of trademarks in discerning the origin of high-quality products becomes more pronounced. This serves to deter imitation or unauthorised utilisation of trademarks. The law is a deliberate set of rules created by society to foster orderly, safe, and peaceful living. As for the conclusion, to secure legal protection, start by applying for trademark registration. If it's discovered that the registered trademark belongs to someone else, the necessary legal step is to initiate a lawsuit to cancel the registered trademark. The development of legal protection for trademark rights is on the rise due to rapid economic growth, resulting in numerous imitations by irresponsible individuals.